Differential regulation of Nrf2 is linked to elevated inflammation and nitrative stress in monocytes of children with autism. (March 2020) - Nadeem, Ahmed; Ahmad, Sheikh F.; AL-Ayadhi, Laila Y.; Attia, Sabry M.; Al-Harbi, Naif O.; Alzahrani, Khalid S.; Bakheet, Saleh A.
Highlights: Nrf2 expression/activity is downregulated in monocytes of autistic subjects. Inflammatory/nitrative stress parameters are upregulated in monocytes of autistic children. LPS induces greater inflammation/ nitrative stress in monocytes of autistic children. Activation of Nrf2 by sulforaphane attenuates inflammation/ nitrative stress in monocytes. Abstract: Autism spectrum disorder (ASD) is a very complex neurodevelopmental disorder characterized by deficits in social and communication skills. Innate immune cells like monocytes are believed to play a cardinal role in neuroimmune inflammation and nitrative stress. On the other hand, Nrf2, a basic leucine zipper transcription factor plays a significant role in protecting the immune cells against inflammation and oxidants. However, its role in monocytes of ASD children and typically developing control (TDC) children has not been elucidated in relation with inflammation and nitrative stress. Therefore, this study was undertaken to evaluate Nrf2 expression/activity along with parameters of inflammation (NF k B, IL-6, IL-1β) and nitrative stress (iNOS, nitrotyrosine) in monocytes of ASD/TDC children. Further, sulforaphane (SFN) was utilized as an Nrf2 activator to assess its effect on above said inflammatory and nitrative stress parameters. Our study shows that monocytes of ASD subjects have decreased Nrf2 expression/activity along with increased inflammation and nitrative stress. Further, monocytes from ASD have deficiency in induction of Nrf2 activity upon stimulation with LPS. However, activation of Nrf2 in vitro by SFN reverses LPS-induced effects on inflammation in monocytes by reduction in NF k B signaling. Further, treatment with SFN also reverses LPS-induced effects on nitrative stress (iNOS, nitrotyrosine) in monocytes of ASD subjects. This study propounds the idea that SFN protects against nitrative stress and inflammation by downregulating oxidative stress and inflammation through blockade of NF k B signaling in autistic children. This may be the reason behind reported ameliorative effects of SFN in ASD subjects.